Pluripotent Stem Cells - From the Bench to the Clinic 2016
DOI: 10.5772/62671
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cells and Their Dynamic Niche

Abstract: Cell-seeded implants are a regenerative medicine strategy that aims to replace injured tissue and restore tissue function. Pluripotent stem cells are promising cell candidates for the development of regenerative medicine therapies as they have the ability to selfrenew and commit towards numerous cell types. In vivo, stem cells reside in a dynamic niche, a stem cell-specific microenvironment that possesses chemical, biological and mechanical cues, which drive the stem cell fate and renewal. The connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 349 publications
(392 reference statements)
0
5
0
Order By: Relevance
“…[ 1 ] Tissue engineering strategies using sources of stem cells, either allogeneic or autologous, present promising approaches for cartilage repair in OA patients. To date, researchers have explored various cell sources for cartilage tissue engineering application, including embryonic stem cells [ 2,3 ] and adult stem cells derived from tissues such as bone marrow, [ 4 ] synovium, [ 5 ] and infrapatellar fat pad, [ 6,7 ] among which bone marrow stem cells (BMSCs) are the most intensively investigated. Studies have demonstrated successful chondrogenic induction of BMSCs over various culture protocols such as pellet, [ 8 ] natural hydrogel, [ 4,9 ] and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Tissue engineering strategies using sources of stem cells, either allogeneic or autologous, present promising approaches for cartilage repair in OA patients. To date, researchers have explored various cell sources for cartilage tissue engineering application, including embryonic stem cells [ 2,3 ] and adult stem cells derived from tissues such as bone marrow, [ 4 ] synovium, [ 5 ] and infrapatellar fat pad, [ 6,7 ] among which bone marrow stem cells (BMSCs) are the most intensively investigated. Studies have demonstrated successful chondrogenic induction of BMSCs over various culture protocols such as pellet, [ 8 ] natural hydrogel, [ 4,9 ] and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we evaluated the adherence of hiPSCs to hydrogels supplemented with the native protein crosslinkers, genipin and EGCG, [ 24 , 25 , 45 ] and chose the most appropriate combination for the differentiation studies. When culturing hiPSCs on the pECM hydrogels, different adherence and proliferation levels were obtained, as the hiPSCs are influenced by their immediate surrounding containing specific molecules for their growth and differentiation [ 55 ]. However, all the hydrogels supported hiPSCs culture for at least 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Niche-derived extrinsic stimuli and intrinsically expressed factors regulate stem cell self-renewal and differentiation that provide the foundation for testis homeostasis (Reinwald et al, 2016). Unlike the welldefined and distally localized germline stem cell niche in the gonads of other model organisms, such as Drosophila and C. elegans, the mammalian testis contains many potential germline stem cell niches (in the range of several thousand to 40,000 per testis) (Tegelenbosch and de Rooij, 1993;Shinohara et al, 2001) that are not well characterized, but are believed to be randomly located along the tubules.…”
Section: Cellular Components Of Ssc Nichementioning
confidence: 99%